Implementación de procedimientos operativos estandarizados y de saneamiento para el sacrificio y faenado de cerdos del taller de cárnicos (ESPAM MFL) - Moreira Mendoza, Howard José (2019)
The purpose of the present work was to implement Standardized Operational and Sanitation Procedures in the area of slaughter of pigs from the Meat Workshop at Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López; first a diagnosis was made by applying a list of verification to identify the main sources of microbial contamination, being the most significant, the reception and slaughter operation, since the equipment and utensils were not disinfected prior to their use, besides the pigs were not taken in an inadequate place; microbiological analyzes of Salmonella, E. coli, Mesophilic Aerobics and Staphylococcus aureus were performed, applied in 3 pigs in the period of 3 days during a week in order to detect the lack of microbiological safety. Subsequently, the POE and POES manuals were prepared, which were used to train the staff that slaughters the animals and, in turn, to carry out infrastructure improvements and correct bad hygiene practices. A small improvement was demonstrated by the checklist in the compliance percentages of the GMP, with compliance of 18% before the implementation of the SOPs and POES compared to 43% after its execution. The microbiological results of the before and after the implementation of POE and POES were analyzed by binary logistic regression where it was obtained by means of the omnibus test that all the models predicted for each pathogen were significant because p<0.05. Also, allowing to demonstrate that the implementation of POE and POES favors microbiological safety, with the probability of absence of 62.5% for Staphylococcus aureus, 79.2% for Aerobic mesophiles and 50% for E. coli for the absence of these pathogens.